Sinonasal Undifferentiated Carcinoma (SNUC): From an Entity to Morphologic Pattern and Back Again-A Historical Perspective - Agaimy, Abbas; Franchi, Alessandro; Lund, Valerie J; Skálová, Alena; Bishop, Justin A; Triantafyllou, Asterios; Andreasen, Simon; Gnepp, Douglas R; Hellquist, Henrik; Thompson, Lester D R; Rinaldo, Alessandra; Ferlito, Alfio (Advances in anatomic pathology, 2020)
Since the first description of sinonasal undifferentiated carcinoma (SNUC) as a distinctive highly aggressive sinonasal neoplasm with probable origin from the sinonasal mucosa (Schneiderian epithelium), SNUC has been the subject of ongoing study and controversy. In particular, the SNUC category gradually became a "wastebasket" for any undifferentiated or unclassifiable sinonasal malignancy of definite or probable epithelial origin. However, with the availability of more specific and sensitive immunohistochemical antibodies and increasing implementation of novel genetic tools, the historical SNUC category became the subject of progressive subdivision leading to recognition of specific genetically defined, reproducible subtypes. These recently recognized entities are characterized by distinctive genetic aberrations including NUTM1-rearranged carcinoma (NUT carcinoma) and carcinomas associated with inactivation of different members of the SWI/SNF chromatin-remodeling gene complex such as SMARCB1-deficient and less frequently SMARCA4-deficient carcinoma. The ring became almost closed, with recent studies highlighting frequent oncogenic IDH2 mutations in the vast majority of histologically defined SNUCs, with a frequency of 82%. A review of these cases suggests the possibility that "true SNUC" probably represents a distinctive neoplastic disease entity, morphologically, phenotypically, and genetically. This review addresses this topic from a historical perspective, with a focus on recently recognized genetically defined subsets within the SNUC spectrum.
Keywords: gen SMARCB1; Maxillary Sinus Neoplasms; Nuclear Proteins; nádory sinu maxillaris; Biomarkers, Tumor; lidé; SMARCB1 Protein; nádorové biomarkery; DNA-helikasy; jaderné proteiny; transkripční faktory; DNA Helicases; Transcription Factors; Carcinoma; karcinom; Humans